2013
DOI: 10.1111/aas.12213
|View full text |Cite
|
Sign up to set email alerts
|

Single dilator vs. guide wire dilating forceps tracheostomy: a meta-analysis of randomised trials

Abstract: GWDF technique is associated with a higher incidence of intraprocedural bleeding and of technical difficulties in completing the procedure (difficult cannula insertions/difficult dilations or failures) compared with the SDT technique. No differences were identified in mid-term and long-term complications. Further studies comparing SDT and GWDF in the general population and in subgroups of high-risk patients (like obese or hypoxaemic patients) are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
0
18
0
1
Order By: Relevance
“…However, single dilatation percutaneous technique was suggested due to low complication rate and it is demonstrated that GWDF was a faster method than CBR [16, 23, 24]. Yet, Cabrini et al showed that there was no difference between mid and long term complications of single dilatation and GWDF techniques [25]. We also found that GWDF (70.4%) was often used as EPT technique in Turkey (Table 2).…”
Section: Discussionmentioning
confidence: 61%
“…However, single dilatation percutaneous technique was suggested due to low complication rate and it is demonstrated that GWDF was a faster method than CBR [16, 23, 24]. Yet, Cabrini et al showed that there was no difference between mid and long term complications of single dilatation and GWDF techniques [25]. We also found that GWDF (70.4%) was often used as EPT technique in Turkey (Table 2).…”
Section: Discussionmentioning
confidence: 61%
“…They also found that the STD was associated with fewer complications and failures. In a later analysis, the same authors reported less operative bleeding and fewer technical difficulties associated with the STD technique than those associated with the GWDF technique (6).…”
mentioning
confidence: 88%
“…Although the short-term complications of these techniques are well described, the prevalence and impact of longer-term outcomes, particularly tracheal stenosis (TS), are unclear. Previous metaanalyses have attempted to address this problem but have been confounded by the low prevalence of TS and, in particular, the limited number of studies reporting long-term outcomes (2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…[26][27][28][29][30] A meta-analysis of these trials found evidence of superiority of the Ciaglia technique using a combined endpoint representing procedural difficulties and bleeding. 31…”
Section: Griggs Techniquementioning
confidence: 99%